Factors that Influence the Increase in Business Income in the MSMEsCommunity of the Leather Industry Center of Yogyakarta City - Eso Hernawan; FX. Pudjo Wibowo; Agus Kusnawan; Rinintha Parameswari; Andy Andy (eCo-Buss, 2024)
The research aims to evaluate the impact of independent variables (product, price, distribution, and promotion ) on the dependent variable, which is the economic business income of MSMEs at the Yogyakarta City Leather Industry Center. This study surveyed 100 consumers from the MSMEs at this industrial center. The sample was selected using simple random sampling, and statistical data analysis was conducted using SPSS 25. The T-test results showed that each independent variable individually exerts a positive and significant effect on the dependent variable, the economic business income of the Yogyakarta MSME community. The calculated t values for the product, price, distribution, and promotion were 2.602, 2.111, 6.101, and 6.648, respectively, all exceeding the t-table value of 1.65, with probabilities of 0.011, 0.037, 0.000, and 0.000, respectively, all below the 0.05 threshold. Additionally, the F-test results indicated that the combined influence of the independent variables on the dependent variable was significant, with an F calculated value of 128.419 surpassing the F-table value of 3.87, and a probability value of 0.000, which is less than 0.05. Thus, it can be concluded that the independent variables collectively have a positive and significant impact on the economic business income of the MSME community.